Analysis of Crude Fiber and Crude Protein Fermented Corn Cob for Animal Feed - Ilham Ahmad; Subhan Effendi; Morse Kathryn; Woolnough Cale (Yayasan Adra Karima Hubbi, 2023)
Low productivity of ruminants due to many factors and one of them is lack of feed ingredients in quality and sustainable in quantity. One of sources can be an alternative feed ingredients that containing fibers as a substitute of grass is corn cobs which becoming other earnings of corn farmers. The aim of this research is going to determine the effect of using EM4 on nutritional (contents of crude protein and crude fiber) fermentation quality of corncobs. The experimental design used a Completely Randomized Design (CRD) with 4 treatments and 3 times replication, treatment J0 = corncobs with no fermentation (control); J1 = fermentation corncobs with EM4 (500 ml); J2 = corncobs fermented with EM4 (700 ml); J3 = fermentation corncobs with EM4 (500 ml). Treatment effects was analyzed by analysis of variance (ANOVA) and followed by a test (DUNCAN) if only known there is a significant effect among the treatments. The results showed that the lowest crude fiber content in treatment J3 (38.41) and the highest in J0 (46.01) was significantly different with treatment J1 (42.49) and J2 (40.81). The Lowest of protein content is in treatment J0 (2.88) and the highest in J3 (8:02) significantly different with treatment J1 (3.65) and J2 (4:27). The best treatment of this research is contained in fermented corn cob with EM4 with the in 900 ml.